2022
DOI: 10.1038/s41598-022-14244-4
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between traction spurs, Modic change, vacuum phenomenon, and segmental instability of the lumbar spine

Abstract: A thorough understanding of lumbar segmental motion is valuable to treat patients with degenerative lumbar disease, but kinematics associated with indicators of lumbar intervertebral instability [traction spur, Modic changes (MCs) and vacuum phenomenon (VP)] in the lumbar spine have not been well understood. The purpose of this study is to evaluate the relationships between traction spur, MCs and VP to radiographic measurements in the lumbar spine. A total of 525 lumbar discs from L1-2 to L5-S1 of 105 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Different authors using the PCD technique agree that advanced disc degeneration with IVP is potentially the main cause of LBP. This mechanical stabilization effect has also been demonstrated in patients with degenerative scoliosis, where the presence of IVP leads to the “accordion phenomenon,” resulting in an increase in curve scoliosis, when the patient is in an orthostatic position compared with the horizontal non-weight bearing X-rays of a CT scan, mainly due to the collapse effect of empty discs with IVP, especially in the concave side (26).…”
Section: Discussionmentioning
confidence: 83%
“…Different authors using the PCD technique agree that advanced disc degeneration with IVP is potentially the main cause of LBP. This mechanical stabilization effect has also been demonstrated in patients with degenerative scoliosis, where the presence of IVP leads to the “accordion phenomenon,” resulting in an increase in curve scoliosis, when the patient is in an orthostatic position compared with the horizontal non-weight bearing X-rays of a CT scan, mainly due to the collapse effect of empty discs with IVP, especially in the concave side (26).…”
Section: Discussionmentioning
confidence: 83%
“…Frequently, both traction and claw spurs coexist on the same vertebral margin. Several investigations have examined the relationship between traction spurs and lumbar segmental instability (Figure 1) [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Our study evaluated early, subtle changes present in MRI indicative of instability, and traction spurs are widely accepted as suggestive of long-standing instability. 4 A review of the work cited 5 showed an association between traction spurs and sagittal translation but not with disc height; no association between vacuum phenomenon and sagittal translation and possible association with disc height. Again, thank you for your interest in our work and for continuing an ongoing discussion on the markers of segmental instability of the lumbar spine.…”
mentioning
confidence: 99%